miR-3587 Inhibitor Attenuates Ferroptosis Following Renal Ischemia-Reperfusion Through HO-1 - Tao, Wenqiang; Liu, Fen; Zhang, Jianguo; Fu, Shangmiao; Zhan, Hui; Qian, Kejian (Frontiers in Molecular Biosciences, 2022)
Renal ischemia-reperfusion (IR) is frequently observed in patients who are critically ill, yet there are no reliable or effective approaches to treating this condition. Ferroptosis, a form of programmed cell death, is regulated by key molecules such as glutathione peroxidase 4 (GPX4) and heme oxygenase-1 (HMOX1), and participates in the injury process of renal tubular epithelial cells in IR. This study aimed to investigate the miRNA-mRNA regulatory networks that are involved in ferroptosis following renal IR. Through bioinformatic analysis, HMOX1 was identified as a key gene that was significantly upregulated during the early stages of renal IR injury, and miR-3587 was identified as a putative regulator of HMOX1. When a miR-3587 inhibitor was applied in a hypoxia-reoxygenation model system using renal tubular epithelial cells, HO-1 (encoded protein by HMOX1 gene) expression was significantly increased relative to that observed in the control group, with concomitant increases in GPX4 protein levels, enhanced cell viability, a reduction in malondialdehyde content, decreased Fe2+ level, and the restoration of normal mitochondrial membrane potential. Luciferase reporter gene assay confirmed that there was a targeted relationship between miR-3587 and HMOX1. Preliminary evidence suggests that utilizing miR-3587 inhibitors can promote HO-1 up-regulation, thereby protecting renal tissues from IR-induced ferroptosis.